2013
DOI: 10.3109/14767058.2013.851186
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of interleukin-6, interleukin-8 and interleukin-18 count in the serum of IUGR newborns

Abstract: An elevated level of IL-6 and IL-18 in the IUGR group, comparing to control group, signifies the existence of inflammation in the process of developing IUGR, therefore, screening tests estimating levels of interleukins as IL-6 and IL-18 might be clinically useful in predicting the occurrence of IUGR and help preventing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Spontaneous miscarriages have also been found to be associated with higher first and second trimester IL‐6 levels, showing an increased rate of miscarriages in pregnant women with IL‐6 levels above 1.725 pg/mL . Additionally, consistent with our results, previous studies have shown a relationship between PPROM and increased IL‐6 levels in maternal serum and cervicovaginal fluid during 24‐37 th weeks of gestation, as well as increased IL‐6 levels in the serum of IUGR neonates when compared with controls …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Spontaneous miscarriages have also been found to be associated with higher first and second trimester IL‐6 levels, showing an increased rate of miscarriages in pregnant women with IL‐6 levels above 1.725 pg/mL . Additionally, consistent with our results, previous studies have shown a relationship between PPROM and increased IL‐6 levels in maternal serum and cervicovaginal fluid during 24‐37 th weeks of gestation, as well as increased IL‐6 levels in the serum of IUGR neonates when compared with controls …”
Section: Discussionsupporting
confidence: 91%
“…14,15 Additionally, consistent with our results, previous studies have shown a relationship between PPROM and increased IL-6 levels in maternal serum and cervicovaginal fluid during 24-37 th weeks of gestation, as well as increased IL-6 levels in the serum of IUGR neonates when compared with controls. 18,19,26 Because of the potential benefits of the early prediction of adverse pregnancy outcomes, mainly in SCH and/or thyroid-Ab positive patients, it is of critical importance to determine a category of patients in which IL-6 levels should be measured. The results of our study indicate no statistically significant differences in overall pregnancy complications in both thyroid-Ab positive and negative pregnancies or in SCH and euthyroid pregnancies, with the exception of PPROM.…”
Section: Discussionmentioning
confidence: 99%
“…Since ferritin is an acute phase reactant and increases during inflammatory processes, an association between IUGR, inflammation, and increased maternal serum ferritin is also plausible. Previous studies also revealed an association between inflammation and fetal growth restriction [19,20]. Increased serum inflammatory markers were detected in growth restricted infants on postnatal day 14 [21].…”
Section: Discussionmentioning
confidence: 77%
“…TNF-α and IL-1β are prototype pro-inflammatory cytokines involved in the pathogenesis of sepsis [28]. IL-6, a kind of pro-inflammatory cytokine, is also associated with continuous intrauterine hypoxia, which is a reason for the occurrence of IUGR [29]. In the current study, IUGR increased the levels of serum TNF-α, IL-1β, and IL-6 in weaned piglets, which might strongly suggest that inflammatory response existed in the piglets.…”
Section: Discussionmentioning
confidence: 99%